Utilization of valorised wood bark waste as an adsorbent for the uptake of Pb(II) ions - Salah Ud Din; Ibrahim Arogundade; Khairia Mohammed Al-Ahmary; Saedah R. Al-Mhyawi; Hamad AlMohamadi; Nuha Y. Elamin; Ibtehaj F. Alshdoukhi; Jawaher Saud Alrashood (Scientific Reports)
Abstract This study investigates the potential of valorized wood bark waste as an efficient, low-cost adsorbent for removing Pb(II) ions from aqueous solutions. Valorization via pyrolysis significantly enhanced the surface area (from 105.3 to 344.7 m²/g) and pore volume (from 0.168 to 0.421 cm³/g), promoting higher adsorption capacity. Characterization using FT-IR, SEM-EDS, BET, and TGA confirmed structural and chemical modifications that improved Pb(II) uptake. Batch experiments optimized parameters such as pH (optimal at 5), contact time (100 min), temperature (55 °C), and adsorbent dosage (0.5 g). The valorized adsorbent (VWBWA) demonstrated superior performance, achieving a maximum adsorption capacity of 114.03 mg/g, nearly twice that of the raw form (59.20 mg/g). Adsorption followed both Langmuir and Freundlich isotherms, and kinetic data fit pseudo-second-order and intraparticle diffusion models, indicating chemisorption and pore diffusion mechanisms. Thermodynamic analysis revealed the process was spontaneous and endothermic, with higher enthalpy (39.54 kJ/mol) and entropy (13.44 J/mol·K) changes for VWBWA. Desorption studies confirmed reusability, with acetic acid showing optimal elution. These findings establish valorized wood bark waste as a promising and sustainable biosorbent for lead remediation in industrial wastewater treatment, aligning with circular economy and waste valorization principles.